Pin-on-disc tribotests with the addition of Cu particles as an interfacial media: Characterization of disc tribosurfaces using SEM-FIB techniques. (August 2016) - Rodrigues, A.C.P.; Yonamine, T.; Sinatora, A.; Azevedo, C.R.F.
Abstract: The present paper focuses on the effect of Cu addition (400 μm, 20 μm and 50 nm) on the microstructure and topography of discs after pin-on-discs tribotests (steel/steel). These results were compared with the condition without any particulate addition. SEM, FIB, EDS and XEDS techniques were used to characterize the discs' tribosurfaces. X-ray mapping characterization showed O associated with Fe adhered to the tribosurfaces for all conditions. Additionally, expressive adhesion of Cu particles on the disc tribosurface was detected via FIB combined with XEDS mapping for the 20 μm and 50 nm conditions. The formation of a compact iron oxide layer on the discs´ tribosurface was only observed for the 400 μm Cu condition and without any Cu addition. Highlights: The addition of Cu particles on pin/disc tribotests was studied. The transfer layer was characterized using focused ion beam, EDS, and XEDS mapping. The formation of an oxide non-compact layer on the disc׳s surface was observed. The adhesion of Cu-rich debris was observed on the disc׳s surface of some systems.